Book cover as intersemiotic translation: between image, text and culture. Issue 3 (2nd September 2021) - Jiang, Mengying
ABSTRACT: This paper starts with an interest in the book cover of the English translations of the Nobel laureate Mo Yan. Except for the covers published by Penguin Books, the design of many other covers fails to convey the essential information of the text. Instead, they are translated from the cultural imaginings of the Chinese culture. Focusing on the relationship between the cover image, text and culture, this paper argues that book cover of translated literature, other than being text-to-cover translation, is also a translation of foreignness, whereby the literary representation of the other culture is being interpreted and constructed. On closer examination of the patterned images of Chinese women, peasants and chubby baby boys on Mo's book covers, this paper explores how such graphical features can be tropes of exoticism under a seemingly perpetuated Orientalist framework and thus reinforce the stereotypical images of China. By highlighting the influence of culture on cover designs of literary translation, this study complements the binary text-to-cover intersemiotic framework with a cultural perspective and aims to reveal (at least partially) the interpretative mechanism underlying the visual representation of literary translation.